Glass for packaging titanium-containing metal material device as well as preparation method and application of glass
By adjusting the glass components, the sealing temperature of glass for packaging devices with titanium-containing metal materials is reduced, and its chemical stability and mechanical strength are improved, and the application problems in the prior art are solved, which are difficult to meet the high temperature, high pressure and corrosive environments, and higher reliability and applicability are achieved.
Patent Information
- Application Number
- CN202411887004.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-20
AI Technical Summary
It is difficult to prepare a glass for packaging of titanium-containing metal materials. The sealing temperature is lower than the crystal transformation temperature of the titanium alloy, and has good chemical stability, mechanical strength and corrosion resistance, which can meet the application in high temperature, high pressure and corrosive environments.
By adjusting the ratio of glass components, including Al2O3, B2O3, CaO, SiO2, Co2O3, TiO2, MgO, ZnO and ZrO2, the sum of mass percentages of Al2O3 and B2O3 is ensured to be less than 75%, and the content of sodium and potassium ions are avoided in the glass to reduce the sealing temperature of the glass and improve chemical stability.
The sealing temperature of the glass is lower than the crystal transformation temperature of the titanium alloy, the chemical stability and mechanical strength of the glass are improved, the tolerance to high-temperature, high-pressure and corrosive environments is enhanced, and the high-reliability use requirements for titanium-containing metal materials are met in high-temperature environments.
Smart Images

Figure CN119874197A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of sealing glass, and in particular relates to glass for packaging titanium-containing metal material devices, and a preparation method and application thereof. Background Art
[0002] Titanium-containing metal materials have the characteristics of low density, high strength, high temperature resistance, corrosion resistance, high mechanical strength, etc. In addition, titanium alloy is a non-magnetic material. When used in the process of transmitting signals, the transmission signal loss is small and it can resist strong magnetic environment interference. It is precisely based on the above characteristics of titanium and titanium alloys that in recent years, they are often used as connectors or sensors and other electronic components shell materials, replacing traditional Kovar alloys, stainless steel, and high-temperature alloys, and are widely used in aviation, aerospace, navigation, oil exploration, electronic information, medical technology and other fields.
[0003] When the sealing temperature of the glass used to encapsulate titanium-containing metal devices is too high, the crystal form of the titanium-containing metal material is easily transformed during the packaging process. At present, researchers in this field are trying to prepare low-temperature glass with a low sealing temperature so that its sealing temperature is below 600°C to avoid the crystal form transformation of the titanium-containing metal material during the packaging process.
[0004] There is a document that prepared a borosilicate titanium alloy sealing glass. By adding a high content of Na2O and K2O, the glass sealing temperature reached 700-825°C and the glass transition temperature T g The temperature ranges from 450 to 650°C respectively, but the chemical stability of the glass prepared therefrom deteriorates and the high-temperature insulation resistance decreases, which also makes it difficult to meet the application requirements of titanium-containing metal materials in high-temperature, high-pressure and corrosive environments. Summary of the invention
[0005] The main purpose of the present invention is to provide a glass for packaging titanium-containing metal material devices and a preparation method and application thereof. The technical problem to be solved is how to provide a glass for packaging titanium-containing metal material devices, so that its sealing temperature is lower than the crystal transformation temperature of the titanium-containing metal material, and it has good chemical stability, high mechanical strength, and good corrosion resistance, and can meet the application of titanium-containing metal materials in high temperature, high pressure, and corrosive environments.
[0006] The purpose of the present invention and the technical problem solved are achieved by adopting the following technical solutions. According to the glass for packaging titanium-containing metal materials, the glass comprises, by mass percentage of oxides: 10-25% Al2O3; 40-60% B2O3; 10-30% CaO; 1-8% SiO2; 0.1-2% Co2O3; 1-5% TiO2; 1-5% MgO; 1-10% ZnO; 0.5-5% ZrO2; and the sum of the mass percentages of Al2O3 and B2O3 is less than 75%.
[0007] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.
[0008] Preferably, in the aforementioned encapsulation glass, the sum of the mass percentages of CaO and MgO is m1; the sum of the mass percentages of Al2O3 and B2O3 is m2; and m1:m2 is 0.15-0.62.
[0009] Preferably, the aforementioned packaging glass further comprises: 0-1.0% Li2O.
[0010] Preferably, the aforementioned encapsulation glass has a sealing temperature of 780-850°C and a glass transition temperature T g 430~620℃; glass softening temperature T f The thermal expansion coefficient at 25-300℃ is 5×10 -6 / ℃~7×10 -6 / ℃; water resistance and chemical stability are above level Ⅳ.
[0011] The purpose of the present invention and the technical problem solved by the present invention are also achieved by the following technical solutions. According to the method for preparing glass for packaging titanium-containing metal material devices proposed by the present invention, the method comprises the following steps:
[0012] Weigh the following raw materials, which include, by weight percentage of oxides, 10-25% Al2O3, 40-60% B2O3, 10-30% CaO, 1-8% SiO2, 0.1-2% Co2O3, 1-5% TiO2, 1-5% MgO, 1-10% ZnO, and 0.5-5% ZrO2; and the sum of the weight percentages of Al2O3 and B2O3 is less than 75%; mix the raw materials uniformly to obtain a batch;
[0013] The batch materials are melted, clarified and homogenized to form molten glass; the molten glass is sequentially quenched and ball-milled to obtain glass powder.
[0014] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.
[0015] Preferably, in the aforementioned preparation method, the melting includes keeping the temperature at 1300-1500° C. for 2-5 hours.
[0016] Preferably, in the aforementioned preparation method, the quenching is tableting quenching.
[0017] Preferably, the aforementioned preparation method further comprises the following steps:
[0018] The glass powder is mixed evenly with a solvent and a binder at a ratio of 100:60 to 80:6 to 10, granulated, pressed and formed; the binder is removed and vitrified to prepare prefabricated glass;
[0019] The solvent is any one or more mixtures of water, alcohol and ethyl acetate; the binder is polyethylene glycol and / or polyvinyl alcohol; the molecular weight of the binder is 5000-40000.
[0020] Preferably, the aforementioned preparation method, in which a gradient temperature method is used for debinding and vitrification, comprises: a first stage, heating to 150-300°C and keeping warm for 1-3 hours; a second stage, continuing to heat to 300-450°C and keeping warm for 1-3 hours; a third stage, continuing to heat to 680-750°C and keeping warm for 15-30 minutes; and then cooling to obtain prefabricated glass.
[0021] The purpose of the present invention and the technical problems solved by the present invention are also achieved by the following technical solutions. According to the preparation method of the titanium-containing metal material packaging device proposed by the present invention, it comprises: using the glass described in the above solution, assembling it with a titanium-containing metal material shell, a Kovar pin, and a graphite mold to form an assembly; placing the assembly in a nitrogen or argon environment for sintering, heating it to 780-850°C; keeping it warm for 0.5-1h; and then cooling it to below 100°C to obtain a finished product.
[0022] By means of the above technical solution, the glass for packaging titanium-containing metal material devices and the preparation method and application thereof proposed in the present invention have at least the following advantages:
[0023] 1. The present invention provides a glass for packaging titanium-containing metal material devices and a preparation method thereof. The sealing temperature of the glass is reduced by adjusting the glass components. Sodium ions and potassium ions are avoided in the glass components, thereby reducing the number of mobile conductive ions in the glass and improving the chemical stability and high-temperature insulation performance of the glass. The sealing temperature of the glass finally obtained is lower than the crystal transformation temperature of the internal elements of the titanium-containing metal material, thereby reducing the surface tension, and its thermal expansion coefficient is well matched with the corresponding coefficient of the titanium-containing metal material, thereby improving the wettability of the glass with the titanium-containing metal material. The glass has high softening temperature and transition temperature, thereby widening the application temperature range of the packaged device. Therefore, the glass for packaging titanium-containing metal material devices provided by the present invention is more practical and has good application prospects.
[0024] 2. The present invention provides an application of glass for packaging titanium-containing metal material devices. During the packaging process, there is no need to apply external force to the glass body for compression and sintering, which reduces the operation process and improves production efficiency and yield rate. The sintering temperature during sealing is low, which avoids the problem of shell deformation caused by titanium alloy crystal phase transformation during traditional silicate glass sealing, and at the same time reduces the energy consumption required for packaging.
[0025] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is an expansion curve diagram of the glass for titanium metal material device packaging prepared in Example 3, which includes the glass expansion coefficient, transition temperature and softening temperature at 25-300°C. DETAILED DESCRIPTION
[0027] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a glass for packaging titanium-containing metal material devices and its preparation method and application proposed by the present invention in combination with the preferred embodiments. Its specific implementation method, structure, characteristics and effects are described in detail as follows.
[0028] The inventors have found through research and analysis that the low-temperature glass for titanium-containing metal material device packaging prepared by the prior art has poor chemical resistance and mechanical strength and weak corrosion resistance due to the high amount of sodium and potassium elements in its glass components. When used for titanium-containing metal material device packaging, the titanium-containing metal material device prepared by the glass has poor insulation, especially at a high temperature such as 350°C, and its insulation performance is far less than 1×10 8 Ω, even lower than 1×10 6 Ω; moreover, when the sealing glass is used in the sealing process of titanium-containing metal materials, the formed device will leak in a high temperature (≥350°C) environment, and thus cannot meet the requirements of using titanium-containing metal materials in high temperature (≥350°C), high pressure, and corrosive environments. However, at present, titanium alloy TC4 materials often maintain a working state for a long time under a temperature of 350°C. 11 The material often maintains working condition for a long time under the temperature condition of 500° C. It can be seen that the low temperature sealing glass prepared by the prior art is limited in actual use.
[0029] The inventors have also conducted further in-depth research and analysis and found that the prior art has publicly prepared high-temperature sealing glass, whose sealing temperature is above 900°C. When the sealing glass prepared by the document is used to encapsulate titanium-containing metal materials, the temperature required for heat treatment needs to reach above 900°C, and the transition temperature between the crystal forms (α, β) of titanium alloy is 882°C. During the encapsulation process, the heat treatment temperature exceeds the transition temperature between the crystal forms (α, β) of titanium alloy, and the crystal form of titanium alloy changes, and its internal microstructure changes, causing its mechanical strength and stability and other properties to drop sharply. In addition, titanium-containing metal materials are easily oxidized under high temperature conditions, and a complex type and thick oxide layer will be formed on its metal surface, which will further reduce the sealing performance of the connector and increase the difficulty of subsequent surface treatment. When the sealing temperature is too high, the silicate, phosphate and other components contained in the glass will produce titanate composite phases and products such as O, H, and N atoms at the titanium alloy interface. These substances will enter the surface of the titanium alloy and cause the alloy to become brittle, which will eventually lead to a decrease in the strength of the material itself and the connector and a decrease in sealing performance.
[0030] Based on the above findings, the inventors intend to design and research a new glass for packaging titanium-containing metal material devices, avoiding the presence of sodium and potassium elements in the glass, and adjusting the formula to make its sealing temperature lower than the crystal transformation temperature of the internal elements of the titanium-containing metal material, and to make it resistant to high temperature, high pressure, and corrosion, so as to meet the requirements of high-reliability use of titanium-containing metal material devices in high-temperature, high-pressure, and corrosive environments.
[0031] The present invention provides a glass for packaging titanium-containing metal material devices, wherein Al2O3, B2O3, CaO, SiO2 and MgO are added to the glass to reduce the sealing temperature of the sealing glass; Co2O3 is also added to the glass to reduce the sealing temperature of the glass, promoting good wettability of the glass and the titanium-containing metal material during the sealing process, thereby helping to ensure good sealing of the sealing glass. In addition, the present invention also improves the chemical resistance of the glass by adding ZnO and ZrO2; in order to make the titanium-containing metal material and the glass better matching, help improve the chemical stability of the glass, and improve the wettability of the glass and the titanium-containing metal material, the present invention also adds TiO2 to the glass.
[0032] The following is an explanation of the range of each component (ingredient) of the glass material of the present invention. In the present invention, unless otherwise specified, the content of each component and the total content are all expressed in mass percentage, i.e., the content of each component and the total content are the mass percentage of the total amount of the glass material converted into oxide composition.
[0033] The present invention provides a glass for device packaging containing titanium metal material, which comprises, by oxide mass percentage, 10-25% Al2O3; 40-60% B2O3; 10-30% CaO; 1-8% SiO2; 0.1-2% Co2O3; 1-5% TiO2; 1-5% MgO; 1-10% ZnO; 0.5-5% ZrO2; and the sum of the mass percentages of Al2O3 and B2O3 is less than 75%. In some embodiments, the titanium-containing metal material is a titanium metal material or a titanium alloy material.
[0034] As a glass network intermediate, Al2O3 can increase the stability of the network, reduce the thermal expansion coefficient of glass, and improve the chemical stability of glass. However, if its content is too high, it may increase the melting difficulty and sealing temperature of the glass. Therefore, the present invention strictly limits the content of Al2O3 to 10-25%.
[0035] B2O3 is a glass network former. As a skeleton structure, it can improve the glass forming properties of glass, reduce the sealing temperature of glass, and improve the sealing ability between glass and titanium metal materials. If its content is too low, the sealing temperature of glass may not meet the preset requirements; but if its content is too high, the chemical stability of glass may be reduced. Therefore, the present invention strictly controls the content of B2O3 to 40-60%.
[0036] When the contents of Al2O3 and B2O3 are high, most of the B2O3 in the glass exists as triangles [BO3], while Al2O3 exists as aluminum oxide octahedrons [AlO6], which reduces the degree of glass network connection and may lead to reduced water resistance and chemical stability of the glass. Therefore, the present invention strictly limits the sum of the contents of Al2O3 and B2O3 to less than 75%.
[0037] SiO2 is an important component of the basic skeleton structure of glass. The present invention strictly limits the mass percentage of SiO2 in glass to 1-8% to maintain the strength and chemical stability of glass, glass viscosity and thermal expansion coefficient and other properties. If the content of SiO2 in glass is less than 1%, the strength and chemical stability of glass may deteriorate; if the content of SiO2 in glass is higher than 8%, the viscosity of glass will increase, the sealing temperature will rise, and the expansion coefficient will be too low, which may cause the expansion coefficient of glass to be unable to match the titanium-containing metal material for packaging.
[0038] CaO and MgO are the outer bodies of the glass network, providing free oxygen, Ca + Mg +It can fill the network gap and produce "mixed alkaline earth effect" and suppression effect to improve the insulation performance of glass; both can increase the chemical stability of glass, and can also effectively reduce the viscosity of glass, making the glass easy to melt and clarify. If its content is too low, the sealing temperature of the glass may not meet the preset requirements; but if the content is too high, the water-resistant chemical stability of the glass will be reduced, and it may also cause the problem of reduced insulation performance. Therefore, the present invention strictly controls CaO to 10-30%; MgO to 1-5%.
[0039] Co2O3 partially enters the glass network, reduces the interface energy between the sealing glass and the titanium-containing metal material, and significantly improves the various properties of the sealing glass; however, when its content is too high, it will hinder the improvement of the sealing performance between the sealing glass and the titanium-containing metal material. Therefore, the present invention strictly controls its content to 0.1-2%.
[0040] ZrO2 can significantly improve the acid, alkali and water resistance of glass, but if its content is too much, the glass will be difficult to melt and clarify, and the sealing temperature may increase. Therefore, the present invention strictly stipulates that the content of ZrO2 is 0.5-5%.
[0041] Preferably, in the aforementioned technical scheme, the sum of the mass percentages of CaO and MgO is m1; the sum of the mass percentages of Al2O3 and B2O3 is m2; and m1:m2 is 0.15-0.62; under this condition, it helps to ensure that the glass has good water-resistant chemical stability, high-temperature insulation, high mechanical strength and good pressure resistance.
[0042] Preferably, in some embodiments of the aforementioned scheme, the glass for packaging titanium-containing metal material devices further includes 0-1.0% Li2O; adding an appropriate amount of Li2O helps to improve the chemical stability of the glass, reduce the viscosity and sealing temperature of the glass, and reduce the crystallization tendency of the glass, but if its content is too much, it is not conducive to reducing the chemical stability of the glass, and the thermal expansion coefficient of the glass may increase, thereby making the sealing glass and the titanium-containing metal material poorly compatible, thereby affecting the sealing performance of the sealing glass and the titanium-containing metal material.
[0043] The glass for packaging titanium-containing metal material devices provided by the present invention has a sealing temperature of 780-850°C; a glass transition temperature T g 430~620℃; glass softening temperature T f The thermal expansion coefficient at 25-300℃ is 5×10 -6 / ℃~7×10 -6 / ℃; water resistance and chemical stability are above level Ⅳ.
[0044] The present invention also provides a method for preparing glass for packaging titanium-containing metal materials, which comprises the following steps:
[0045] 1) Prepare glass powder, the preparation method is as follows:
[0046] Preparation of batch material: Weigh the following raw materials, calculated by oxide mass percentage, including: 10-25% Al2O3; 40-60% B2O3; 10-30% CaO; 1-8% SiO2; 0.1-2% Co2O3; 1-5% TiO2; 1-5% MgO; 1-10% ZnO; 0.5-5% ZrO2; and the sum of the mass percentages of Al2O3 and B2O3 is less than 75%. Mix the raw materials evenly to obtain the batch material.
[0047] Preferably, in some embodiments, the sum of the mass percentages of CaO and MgO is m1; the sum of the mass percentages of Al2O3 and B2O3 is m2; and m1:m2 is 0.13-0.62. Further preferably, in other embodiments, the batch material further includes 0-1.0% Li2O.
[0048] Melting: Add the above-mentioned batch materials into a crucible of a high-temperature melting furnace for high-temperature melting. In order to completely melt the batch materials and quickly form a clarified and homogenized glass liquid, the glass liquid is continuously stirred with a stirring rod and kept warm at 1300-1500°C for 2-5 hours. Further preferably, in some embodiments, the melting temperature is 1350-1500°C. Under this temperature condition, the melting efficiency of the glass can be improved.
[0049] The crucible and stirring rod used in the present invention are preferably made of corrosion-resistant materials. In some embodiments, a pure platinum crucible is used, and in other embodiments, a platinum alloy crucible is used.
[0050] Quenching: The glass liquid homogenized in the above scheme is quenched to prepare cullet. Preferably, in some embodiments, tablet quenching is adopted. This is because there are a large number of BO-Ca bonds in the glass of the present invention. If the cullet is prepared by the traditional water quenching method, the BO-Ca group reacts with water to easily generate Ca(OH)2, and the original structure composed of Ca is destroyed. 2+ The charge balance with [BO4] tetrahedron causes Ca(OH)2 to decompose in the later sintering process, which affects the stability of the surface glass network structure. The present invention adopts tablet quenching, and the rotation speed of the tablet press is 20-40rpm, which can avoid contact with water during the glass preparation process, thereby solving the influence of water on the glass structure during the boroaluminate glass forming process and ensuring the stability of the surface glass network structure.
[0051] Ball milling: The broken glass formed by quenching in the above scheme is placed in a ball mill and ball milled to form glass powder. The material of the ball mill is not specifically limited, as long as it can achieve ball milling. In some embodiments, the ball mill is a corundum ball mill. In order to improve the ball milling efficiency, in some embodiments of the present invention, the ball milling speed is 30-50rpm and the ball milling time is 24-28h. In order to make the glass powder formed by ball milling more uniform and finer, preferably, a ball milling solvent is added during the ball milling process. In some embodiments, the ball milling solvent is alcohol, 95% or more ethanol, etc.
[0052] 2) Preparing prefabricated glass, the preparation method thereof is as follows:
[0053] Mixing: The glass powder prepared by the above scheme is mixed evenly with the solvent and the binder at a ratio of 100:60 to 80:6 to 10 to form a mixture. The ratio range of glass liquid to solvent and binder is strictly limited. The binder and the glass powder have good solubility in the solvent and are evenly dispersed, which is conducive to the subsequent bonding and granulation of the glass powder. Preferably, in some embodiments, the glass powder prepared by the above scheme is also sieved through a 150-180 mesh sieve, and the particle size distribution of the particles formed during the granulation process is uniform, which is conducive to the smooth progress of the pressing step.
[0054] Preferably, in some embodiments, the solvent is a mixture of any one or more of water, alcohol, and ethyl acetate; the binder is any one of polyethylene glycol (hereinafter referred to as "PEG") or polyvinyl alcohol (hereinafter referred to as "PVP") or a mixture thereof. The use of these solvents and binders allows the binder and glass powder to be completely dissolved in the solvent, and the binder allows the glass powder to be better bonded to facilitate subsequent granulation and pressing steps. In other embodiments, the molecular weight of the binder is preferably 5000 to 40000; further preferably, the molecular weight of the binder is 6000 to 30000; strictly limiting the molecular weight range of the binder is beneficial to the bonding of the glass powder, and is also beneficial to the subsequent granulation, pressing, debinding and vitrification process steps to proceed smoothly.
[0055] Granulation: Granulate the mixture formed by mixing the glass powder with the solvent and the binder to prepare granules. The granulation method can be any one of a spray drying granulation method, a manual granulation method and a pressure granulation method.
[0056] Preferably, in some embodiments, a spray drying granulation method is used, and the inlet temperature of the atomizing drying equipment during the granulation process is 200-350°C; the outlet temperature is 100-200°C. The present invention preferably uses a spray drying granulation method, and further strictly limits the temperature conditions during the spray drying granulation process, which not only makes the preparation efficiency high, but also helps to obtain particles with uniform particle size. If the temperature is too low, the viscosity of the formed particles is too large, which can easily cause the atomizing drying equipment to be blocked; in addition, if the temperature is too high, the glass components will be carbonized, affecting the various properties of the glass prepared subsequently.
[0057] Preferably, in some embodiments of the aforementioned technical solution, a spray drying granulation method is adopted, and the granules formed by granulation are 50 to 200 meshes, and the particle size of the granules is strictly limited, which is not only conducive to avoiding blockage of the atomization drying equipment and allowing the atomization granulation to proceed smoothly, but also conducive to the smooth progress of the subsequent pressing process.
[0058] Pressing and molding: The granules formed by granulation are pressed and molded. The present invention does not specifically limit the pressing equipment, as long as the pressing and molding can be achieved. In some embodiments, a molding press is used for pressing and molding to form a glass blank. It is further preferred that the rotation speed of the tablet press is 20 to 40 rpm, so that the glass blank can be formed quickly and the molding effect is good.
[0059] Debinding and vitrification: The present invention adopts a gradient temperature method to debind and vitrify the pressed glass blank, which includes: the first stage, heating from room temperature (20-25°C) to 150-300°C at a heating rate of 2-10°C / min, and keeping warm for 1-3h; the second stage, heating at a heating rate of 2-10°C / min, continuing to heat on the basis of the temperature conditions of the first stage, heating to 300-450°C, and keeping warm for 1-3h; the third stage, heating at a heating rate of 10-20°C / min, continuing to heat on the basis of the temperature conditions of the second stage, heating to 680-750°C, and keeping warm for 15-30min; and prefabricated glass is obtained. The above process methods and process parameters are adopted to strictly control the heating rate and insulation temperature conditions of each stage, so as to avoid uneven heating inside the glass due to too fast heating rate or too high temperature, and easy carbonization; and the process preparation parameters of the present invention are also conducive to exhausting the colloid in the glass blank, ensuring that the various properties of the formed prefabricated glass meet the design requirements. The present invention does not specifically limit the device for placing the pressed glass blank for debinding and vitrification, as long as it can achieve debinding and vitrification of the glass blank prepared by the above scheme. Preferably, in some embodiments, the third stage is heated to a temperature within the range of 680-730°C. Under this condition, energy is saved and investment costs are reduced while ensuring that the colloid of the glass blank can be completely drained.
[0060] The present invention also provides a method for preparing a titanium-containing metal material packaging device, which includes assembling the glass described in the above scheme with a titanium-containing metal material shell, a Kovar pin, and a graphite mold to form an assembly; then placing the assembly in a nitrogen or argon environment for sintering, heating up from room temperature (20-25°C) to 780-850°C at a heating rate of 5-20°C / min; keeping warm for 0.5-1h; then cooling down to below 100°C at a cooling rate of 5-10°C / min to obtain a finished product. The present invention strictly limits the heating rate of the sintering process because a too fast heating rate will cause the glass to melt faster, so that there is a gap between the glass and the titanium-containing metal material shell and the contact surface, and gas is trapped in the gap, which makes the titanium-containing metal material packaging device poor in strength, low in sealing, and poor in insulation performance. Preferably, in some embodiments, the heating rate is 5-15°C / min and the cooling rate is 5-8°C / min, which can better ensure that the various performances of the prepared titanium-containing metal material packaging device are good.
[0061] The titanium-containing metal material packaging device prepared by the present invention has a leakage rate of less than 1×10 -10 Pa·m 3 / s; Insulation resistance (350℃)>1×10 8 Ω, excellent performance in all aspects.
[0062] The present invention will be further described below in conjunction with specific embodiments, but this should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.
[0063] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods well known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the common meanings understood by ordinary technicians in the field to which the present invention belongs.
[0064] The testing methods of various performance indicators in the embodiments of the present invention and the comparative examples are as follows:
[0065] Thermal expansion coefficient test: Test according to the method specified in GB / T 7962.16-2010;
[0066] Glass transition temperature T g And glass softening temperature T f Test: According to GB / T 7962.16-2010 colorless optical glass test method;
[0067] Bending strength test: Tested in accordance with GB / T 37781-2019 glass material bending strength test method;
[0068] Water resistance and chemical stability test: Tested in accordance with the water resistance test method and classification of glass particles at 98°C in GB / T6582-2021;
[0069] Sealing temperature test: Test according to the method specified in "SJ / T 3231-2005";
[0070] Leak rate test: Use a helium mass spectrometer leak detector to measure the leakage rate of the sealed product.
[0071] Insulation resistance test: Use an ultra-high resistance tester to measure the insulation of the sealed product at 25°C and 350°C.
[0072] Example 1
[0073] This embodiment prepares a titanium-containing metal material device packaging glass and its preparation method and application. It includes the following steps:
[0074] 1) Preparing prefabricated glass powder, the specific method is as follows:
[0075] S1: Weigh raw materials according to the glass component ratio in Table 1, and mix them evenly to obtain a batch material.
[0076] S2: The batch material prepared in S1 is placed in a platinum crucible in a high-temperature melting furnace, the melting temperature is 1350°C, the temperature is kept for 4 hours, and a platinum stirring rod is used to continuously stir to form a homogenized glass liquid.
[0077] S3: The glass liquid obtained in S2 is quenched by tablet pressing and quenching, and the rotation speed of the tablet press is 30 rpm.
[0078] S4: The broken glass formed in S3 is placed in a corundum ball mill and ball milled. During the ball milling process, an appropriate amount of ball milling solvent is added. The ball milling speed is 40 rpm. The ball milling time is 24 hours to obtain glass powder.
[0079] 2) Preparing prefabricated glass, the specific method is as follows:
[0080] The glass preform is prepared by using the glass powder, which comprises the following steps:
[0081] 1) Mixing: Pass the glass powder through a 160-mesh sieve, and then mix it with water and PEG (PEG molecular weight is 8000) in a mass ratio of 100:70:8 to form a mixture;
[0082] 2) Granulation: spray-dry the mixture formed in step 1) in a spray drying device to form granules with a size of 50 to 200 meshes;
[0083] 3) Pressing and molding: The granules prepared by granulation are pressed and molded by a molding press to form a glass body;
[0084] 4) Debinding and vitrification: The glass blank is debinded and vitrified by using the gradient temperature method:
[0085] The first stage: at room temperature, the temperature is raised to 230°C at a rate of 5°C / min and kept at this temperature for 2 hours;
[0086] Stage 2: Based on the temperature of the first stage, continue to heat up to 400°C at a rate of 5°C / min and keep warm for 2h;
[0087] The third stage: based on the temperature of the second stage, the temperature is further increased to 700°C at a rate of 15°C / min, and kept at this temperature for 15 minutes; then cooled to obtain prefabricated glass.
[0088] 3) Encapsulation and preparation of titanium alloy encapsulation devices, the specific method is as follows:
[0089] The titanium alloy shell, the Kovar pin and the graphite mold are cleaned and dried, and then assembled with the prefabricated glass prepared in this embodiment; then the assembled parts are placed in a nitrogen environment for sintering, the temperature is increased to 800°C at a heating rate of 10°C / min, and the temperature is kept for 0.5h; then the temperature is reduced to below 100°C at a cooling rate of 15°C / min to obtain a finished product.
[0090] 4) Preparation and testing:
[0091] Glass transition temperature T of prefabricated glass g ; Glass softening temperature T f ; Thermal expansion coefficient; Water resistance and chemical stability test; Bending strength; Glass sealing temperature test; Test method as described above.
[0092] The titanium alloy packaged device was tested for leakage rate and insulation resistance (350°C, 25°C). The specific method is as described above. The test results are shown in Table 5.
[0093] Example 2
[0094] The difference between this embodiment and embodiment 1 is that the distribution ratio of each group in the raw materials of this embodiment is as shown in Table 1, the remaining steps and parameters are the same as those of embodiment 1, and the detection indicators and methods are the same as those of embodiment 1.
[0095] Example 3
[0096] The difference between this embodiment and embodiment 1 is that the proportions of the components in the raw materials of this embodiment are shown in Table 1, the remaining steps and parameters are the same as those of embodiment 1, the detection indexes and methods are the same as those of embodiment 1, and the expansion curve of the glass for titanium metal material device packaging prepared in the embodiment is plotted, see Attached Figure 1 .
[0097] Example 4
[0098] The difference between this embodiment and embodiment 1 is that the distribution ratio of each group in the raw materials of this embodiment is as shown in Table 1, the remaining steps and parameters are the same as those of embodiment 1, and the detection indicators and methods are the same as those of embodiment 1.
[0099] Example 5
[0100] The difference between this embodiment and embodiment 1 is that the distribution ratio of each group in the raw materials of this embodiment is as shown in Table 1, the remaining steps and parameters are the same as those of embodiment 1, and the detection indicators and methods are the same as those of embodiment 1.
[0101] Example 6
[0102] The difference between this embodiment and embodiment 1 is that the distribution ratio of each group in the raw materials of this embodiment is as shown in Table 1, the remaining steps and parameters are the same as those of embodiment 1, and the detection indicators and methods are the same as those of embodiment 1.
[0103] Example 7
[0104] The difference between this embodiment and embodiment 1 is that the distribution ratio of each group in the raw materials of this embodiment is as shown in Table 1, the remaining steps and parameters are the same as those of embodiment 1, and the detection indicators and methods are the same as those of embodiment 1.
[0105] Example 8
[0106] The difference between this embodiment and embodiment 1 is that the distribution ratio of each group in the raw materials of this embodiment is as shown in Table 1, the remaining steps and parameters are the same as those of embodiment 1, and the detection indicators and methods are the same as those of embodiment 1.
[0107] Example 9
[0108] The difference between this embodiment and embodiment 1 is that the process parameters of this embodiment are as shown in Table 2, and the rotation speed of the tablet press is 20 rpm during the tablet quenching process; the remaining steps are the same as those of embodiment 1, and the detection indicators and methods are the same as those of embodiment 1.
[0109] Example 10
[0110] The difference between this embodiment and embodiment 1 is that the process parameters of this embodiment are as shown in Table 2, and during the preparation of prefabricated glass, the glass powder is sieved through a 140-mesh sieve; the remaining process parameters and steps are the same as those of embodiment 1, as shown in Table 3 and Table 4.
[0111] Comparative Example 1
[0112] The difference between this comparative example and Example 1 is that the mass percentage of SiO2 in the glass component is 10%, which exceeds the maximum limit of SiO2 in the glass component of the present invention; the remaining components are shown in Table 3, the process parameters are shown in Table 4, and the process steps and parameters are basically the same as those in Example 1.
[0113] Comparative Example 2
[0114] The difference between this comparative example and Example 1 is that the glass component does not contain SiO2; the remaining components are shown in Table 3, the process parameters are shown in Table 4, and the process steps and parameters are basically the same as those in Example 1.
[0115] Comparative Example 3
[0116] The difference between this comparative example and Example 1 is that the mass percentage of B2O3 in the glass component is 63%, which exceeds the maximum limit of B2O3 in the glass component of the present invention; the remaining components are shown in Table 3, the process parameters are shown in Table 4, and the process steps and parameters are basically the same as those in Example 1.
[0117] Comparative Example 4
[0118] The difference between this comparative example and Example 1 is that the mass percentage of CaO in the glass component is 32%, which exceeds the maximum limit of CaO in the glass component of the present invention; the remaining components are shown in Table 3, the process parameters are shown in Table 4, and the process steps and parameters are basically the same as those in Example 1.
[0119] Comparative Example 5
[0120] The difference between this comparative example and Example 1 is that in the process of preparing cullet, the quenching method adopted is the traditional water quenching method, specifically: pouring the molten glass liquid into deionized water, quenching it into glass particles, and then putting it into an oven for drying. The remaining process parameters and steps are the same as those of Example 1, as shown in Tables 3 and 4.
[0121] Comparative Example 6
[0122] The difference between this comparative example and Example 1 is that in the granulation process, the binder used is PEG with a molecular weight of 4000; the other process parameters and steps are the same as those of Example 1, as shown in Tables 3 and 4.
[0123] Comparative Example 7
[0124] The difference between this comparative example and Example 1 is that in the granulation process, the binder used is PEG with a molecular weight of 60,000; the other process parameters and steps are the same as those of Example 1, as shown in Tables 3 and 4.
[0125] In the following tables, Table 1 is the glass composition of each embodiment; Table 2 is the process conditions of each embodiment; Table 3 is the glass composition of each comparative example; Table 4 is the process conditions of each comparative example; Table 5 is the test results of the embodiments and the comparative examples.
[0126] Each component in Table 1 and Table 3 is a mass percentage, and the unit is %. In Table 1 and Table 3, m1 is the sum of the mass percentages of Al2O3 and B2O3; m2 is the sum of the mass percentages of CaO and MgO.
[0127] The meanings of the units and letters in each process stage in Table 2 and Table 4 are as follows:
[0128] Glass powder preparation stage: melting temperature unit: °C; melting time unit: h; ball milling speed unit: rpm; ball milling time unit: h.
[0129] In the prefabricated glass stage, the meanings of the letters are as follows:
[0130] M represents the molecular weight of the binder;
[0131] η represents the ratio of glass powder: water: binder;
[0132] α1 represents the heating rate of the first stage of gradient debinding, in ℃ / min;
[0133] T1 represents the first stage insulation temperature of gradient debinding, unit: °C;
[0134] t1 represents the first stage insulation time of gradient debinding, unit: h;
[0135] α2 represents the heating rate in the second stage of gradient debinding, in ℃ / min;
[0136] T2 represents the second stage insulation temperature of gradient debinding, unit: °C;
[0137] t2 represents the second stage insulation time of gradient debinding, unit: h;
[0138] α3 represents the heating rate in the third stage of gradient debinding, in ℃ / min;
[0139] T3 represents the insulation temperature of the third stage of gradient debinding, in °C;
[0140] t3 represents the insulation time of the third stage of gradient debinding, in min;
[0141] Sealing device stage: the sintering temperature unit is ℃; the units of heating rate and cooling rate are both ℃ / min.
[0142] In Table 5, the meanings of the letters are as follows:
[0143] α: indicates the thermal expansion coefficient of glass at 25-300°C, in units of ×10-7 / ℃;
[0144] T g : represents the glass transition temperature, unit is ℃;
[0145] T f : Indicates the softening temperature of glass, unit: °C;
[0146] T 封 : Indicates the sealing temperature of the packaged device, unit: °C;
[0147] Water resistance and chemical stability: refer to GB / T6582-2021 water resistance classification of glass particles at 98°C;
[0148] Leakage rate: indicates the leakage rate of the packaged device, the unit is ×10 -10 Pa·m 3 / s;
[0149] Insulation resistance (350℃): Indicates the insulation resistance of the packaged device at 350℃, the unit is ×10 8 Ω;
[0150] Insulation resistance (25°C): Indicates the insulation resistance of the packaged device at 25°C, the unit is ×10 14 Ω;
[0151] Bending resistance: indicates the bending strength of glass, the unit is MPa;
[0152] -Indicates that the relevant data could not be or were not tested.
[0153] Table 1 Ratio of raw material components in each example
[0154]
[0155] Table 2 Process conditions for preparing glass powder in various examples
[0156]
[0157]
[0158] Table 3 Ratio of raw material components in each comparative example
[0159]
[0160] Table 4 Preparation process conditions of each comparative example
[0161]
[0162]
[0163] Table 5 Test results of embodiments and comparative examples
[0164]
[0165]
[0166] Combined with the embodiments and the data in Tables 1, 2, and 5, and the attached Figure 1 It can be seen that the glass for packaging titanium-containing metal materials prepared in the present invention has a sealing temperature of 780-850°C; the glass transition temperature T g 430~620℃; glass softening temperature T f The thermal expansion coefficient at 25-300℃ is 5×10 -6 / ℃~7×10 -6 / ℃; water resistance and chemical stability are above level Ⅳ.
[0167] By comparing Example 10 with Example 1, it can be seen that in the process of preparing prefabricated glass, the particle size of the glass powder is still relatively coarse after screening, and the airtightness of the device of the prepared glass will be reduced after sealing. This is because the glass powder is too coarse and the surface of the glass preform is rougher. During the sealing process, the wettability between the glass and the shell is poor, resulting in reduced airtightness of the device.
[0168] Comparing Comparative Example 1 with Example 1, it can be seen that the mass percentage of SiO2 in the glass component exceeds the maximum limit of SiO2 in the glass component of the present invention, and the sealing temperature of the prepared glass will increase. This is because the increase in SiO2 content improves the compactness of the glass network structure, resulting in an increase in the characteristic temperature point of the glass and the sealing temperature.
[0169] Comparing Comparative Example 2 with Example 1, it can be seen that when the glass component does not contain SiO2, the glass prepared therefrom has the problem of reduced bending strength of the glass. This is because the glass does not contain the network former SiO2, the density of the network structure of the glass is reduced, resulting in reduced bending strength of the glass.
[0170] Comparing Comparative Example 3 with Example 1, it can be seen that the mass percentage of B2O3 in the glass component exceeds the maximum limit of B2O3 in the glass component of the present invention, and the glass prepared therefrom has the problems of poor chemical stability and low bending strength. This is because the glass contains too much B2O3, which basically exists in the glass network structure in the form of boron oxide triangles, which reduces the connection degree of the glass network, makes the glass more easily peeled, and leads to reduced chemical stability and reduced bending strength.
[0171] Comparing Comparative Example 4 with Example 1, it can be seen that the mass percentage of CaO in the glass component exceeds the maximum limit of CaO in the glass component of the present invention, and the prepared glass will have the problem of poor glass chemical stability. This is because a large amount of CaO in the glass provides more free oxygen, which reduces the degree of connection of the glass network structure, making the glass more susceptible to corrosion, resulting in reduced chemical stability.
[0172] Comparing Comparative Example 5 with Example 1, it can be seen that the glass prepared by the traditional water quenching method will have the problem of reduced chemical stability. This is because during the water quenching process, a large number of BO-Ca bonds exist in the glass, and the BO-Ca groups react with water to generate Ca(OH)2, which is easily corroded in a humid environment.
[0173] Comparison of Comparative Example 6 with Example 1 shows that the molecular weight of the binder used is too low and its bonding effect on the glass powder is weak, so the glass preform has the problem of low density and looseness.
[0174] Comparing Comparative Example 7 with Example 1, it can be seen that the molecular weight of the binder used is too large, and its bonding effect on the glass powder is strong, which makes steps such as debinding difficult during the preparation of prefabricated glass, which in turn leads to the problem of unclean removal of organic matter in the prepared glass, and a large number of bubbles appear in the glass body after packaging. The insulation resistance of the glass decreases at high temperatures, and the glass is more easily broken down by electric current.
[0175] The technical features in the claims and / or the specification of the present invention may be combined, and the combination is not limited to the combination obtained by reference in the claims. The technical solution obtained by combining the technical features in the claims and / or the specification is also within the protection scope of the present invention.
[0176] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A glass for packaging titanium-containing metal materials, characterized in that: Calculated in terms of oxide mass percentage, it includes: 10-25% Al2O3; 40-60% B2O3; 10-30% CaO; 1-8% SiO2; 0.1-2% Co2O3; 1-5% TiO2; 1-5% MgO; 1-10% ZnO; 0.5-5% ZrO2; and the sum of the mass percentages of Al2O3 and B2O3 is less than 75%.
2. The glass according to claim 1, characterized in that The sum of the mass percentages of CaO and MgO is m1; the sum of the mass percentages of Al2O3 and B2O3 is m2; m1:m2 is 0.15~0.
62.
3. The glass according to claim 1, characterized in that It also includes: 0-1.0% Li2O.
4. The glass according to claim 1, characterized in that The sealing temperature is 780~850℃; the glass transition temperature T g 430~620℃; glass softening temperature T f The thermal expansion coefficient at 25-300℃ is 5×10 -6 / ℃~7×10 -6 / ℃; water resistance and chemical stability are above level Ⅳ.
5. A method for preparing glass for packaging titanium-containing metal materials, characterized in that: It includes the following steps: Weigh the following raw materials, which include, by weight percentage of oxides, 10-25% Al2O3, 40-60% B2O3, 10-30% CaO, 1-8% SiO2, 0.1-2% Co2O3, 1-5% TiO2, 1-5% MgO, 1-10% ZnO, and 0.5-5% ZrO2; and the sum of the weight percentages of Al2O3 and B2O3 is less than 75%; mix the raw materials uniformly to obtain a batch; The batch materials are melted, clarified and homogenized to form molten glass; the molten glass is sequentially quenched and ball-milled to obtain glass powder.
6. The preparation method according to claim 5, characterized in that: The melting includes keeping the temperature at 1300-1500° C. for 2-5 hours.
7. The preparation method according to claim 5, characterized in that: The quenching is tableting quenching.
8. The preparation method according to any one of claims 5 to 7, characterized in that: It also includes the following steps: The glass powder is mixed evenly with a solvent and a binder at a ratio of 100:60 to 80:6 to 10, granulated, pressed and formed; the binder is removed and vitrified to prepare prefabricated glass; The solvent is any one or more mixtures of water, alcohol and ethyl acetate; the binder is polyethylene glycol and / or polyvinyl alcohol; the molecular weight of the binder is 5000-40000.
9. The preparation method according to claim 8, characterized in that: The debinding and vitrification is carried out by a gradient temperature method, which includes: in the first stage, heating to 150-300°C and keeping warm for 1-3 hours; in the second stage, continuing to heat to 300-450°C and keeping warm for 1-3 hours; in the third stage, continuing to heat to 680-750°C and keeping warm for 15-30 minutes; and then cooling to obtain prefabricated glass.
10. A method for preparing a titanium-containing metal material packaging device, characterized in that: The glass according to any one of claims 1 to 4 is assembled with a titanium-containing metal shell, a Kovar pin, and a graphite mold to form an assembly; the assembly is sintered in a nitrogen or argon environment, the temperature is raised to 780-850°C; the temperature is kept for 0.5-1h; and the temperature is then lowered to below 100°C to obtain a finished product.
Citation Information
Patent Citations
Titanium and titanium alloy-sealing glass material as well as preparation method and application thereof
CN111018352A
Sealing glass
CN114956549A
Sealing glass powder with high expansion coefficient as well as preparation method and application thereof
CN116119933A
Method for manufacturing glass member with sealing material layer and method for manufacturing electronic device
JP2011051811A
Low temperature co-fired ceramic material and preparation method therefor
WO2018040749A1